Decoding Consumer Habits: Analyzing Retail Patterns Across Demographics - Sazib Hossain; Hasna Hena; Precious Sampa (Pandawan Sejahtera Indonesia, 2024)
This study examines consumer habits by analyzing retail patterns across vari- ous demographics using a dataset encompassing 3,900 transactions. The data includes variables such as age, gender, item purchased, purchase amount, loca- tion, and more, allowing for a comprehensive analysis of consumer behavior. Key insights reveal significant trends in purchasing decisions influenced by de- mographic factors like age and gender, as well as external elements such as sea- sonality and promotional activities. The analysis identifies predominant shop- ping preferences among different age groups, highlighting the influence of dis- counts and promotional codes on purchasing behavior. Additionally, the study explores the correlation between customer loyalty, as indicated by subscription status and frequency of purchases, and spending patterns. By decoding these retail patterns, this research provides valuable insights for retailers aiming to optimize marketing strategies and enhance customer engagement through tar- geted interventions. The findings contribute to a deeper understanding of how demographic factors shape consumer behavior, offering actionable insights for businesses seeking to adapt to evolving market demands.